Study of Mechanical Properties and Weldability of Aluminium Alloy and Stainless steel by Gas Metal Arc Welding. (2020) - Sachin, R.; Sumesh, A.; Upas, U.S.
Abstract: Aluminium-Steel joints which find application in the area of aerospace, automotive and shipbuilding industry aims to reduce the weight of structure thereby enhancing the efficiency. Welding is a method of enduringly joining two materials (usual metals) through contained coalescence resulting from a suitable combination of temperature, pressure and metallurgical conditions. There is a huge difference in melting point between Aluminium alloy and steel which makes this a great disadvantage for the process. Conducted an experimental investigation to understand the weldability of Aluminium alloy to stainless steel using the GMAW process. Aluminum alloy A5086 and Stainless steel IS2062 were lap welded using Gas metal arc welding process using two types of fillers which are ER5356 (Set A) and ER308LSi (Set B). A comparison is made between the two types on the basis of their mechanical properties and microstructure of welded joints. The hardness values of the weld in Set A and Set B ranged from 55 to 95 HV and 170 to 220 HV, respectively. By using filler ER5356, a maximum tensile strength of 102.4 MPa was obtained. The tensile strength of Set A ranged between 46.3 to 102.4 which was higher than Set B which ranged between 18.24 to 59.76 MPa. The combination of ER5356 filler and voltage of 18V was the best optimum condition in joining Aluminium alloy A5086 and Steel IS2062 dissimilar metals.